Frustrated tunneling ionization during laser-induced D2 fragmentation: Detection of excited metastable D∗ atoms - McKenna, J.; Zeng, S.; Hua, J. J.; Sayler, A. M.; Zohrabi, M.; Johnson, Nora G.; Gaire, B.; Carnes, K. D.; Esry, B. D.; Ben-Itzhak, I. (My University, 2011)
In a recent Letter, Manschwetus et al. [Phys. Rev. Lett. 102, 113002 (2009)] reported evidence of electron recapture during strong-field fragmentation of H2—explained using a frustrated tunneling ionization model. Unusually, the signature of this process was detection of excited H∗ atoms. We report here an extensive study of this process in D2. Our measurements encompass a study of the pulse duration, intensity, ellipticity, and angular distribution dependence of D∗ formation. While we find that the mechanism suggested by Manschwetus et al. is consistent with our experimental data, our theoretical work shows that electron recollision excitation cannot be completely ruled out as an alternative mechanism for D∗ production.